Hi this question is really bugging me.
Write each expression as a product of three factors
L) ax<sup>2</sup> - a - 2x<sup>2</sup> + 2
= a(x<sup>2</sup> - 1) - 2(x<sup>2</sup> - 1)
= (a - 2)(x<sup>2</sup> - 1)
= (x - 1)(x + 1)(a - 2)
This answer is correct but when I expand it out I get.
x<sup>2</sup> + x + ax -2x - x - 1 -a + 2 +ax -2x + a - 2
= x<sup>2</sup> + 2ax - 4x - 1
If I expand out the difference of two squares bit first and then expand again, I get the right answer.
(x<sup>2</sup> - 1)(a - 2)
= ax<sup>2</sup> - a -2x<sup>2</sup> + 2
Can anyone explain why I can't just expand it all out in one go? I'm worried that in an exam i might miss the difference of two squares and then bugger up the question.
Thank you.
Write each expression as a product of three factors
L) ax<sup>2</sup> - a - 2x<sup>2</sup> + 2
= a(x<sup>2</sup> - 1) - 2(x<sup>2</sup> - 1)
= (a - 2)(x<sup>2</sup> - 1)
= (x - 1)(x + 1)(a - 2)
This answer is correct but when I expand it out I get.
x<sup>2</sup> + x + ax -2x - x - 1 -a + 2 +ax -2x + a - 2
= x<sup>2</sup> + 2ax - 4x - 1
If I expand out the difference of two squares bit first and then expand again, I get the right answer.
(x<sup>2</sup> - 1)(a - 2)
= ax<sup>2</sup> - a -2x<sup>2</sup> + 2
Can anyone explain why I can't just expand it all out in one go? I'm worried that in an exam i might miss the difference of two squares and then bugger up the question.
Thank you.